Attitudes towards knowledge sharing among quantity surveyors - Pow, Yih Wen, 1987-; Kherun Nita Ali, supervisor; Fakulti Alam Bina (2010)
Project Paper (Sarjana Muda Ukur Bahan) - Universiti Teknologi Malaysia, 2010